Senam Otak (Brain Gym) terhadap Peningkatan Fungsi Kognitif pada Lansia dengan Diabetes Melitus Tipe 2 di Puskesmas Singkawang Utara 1 - Niya Fittrasih; Erni Juniartati; Wiradianto Putro (Jurnal Ners, 2025)
Aging is a natural process accompanied by a decline in physical and cognitive functions. Elderly individuals with diabetes mellitus are twice as likely to experience cognitive impairment compared to those without diabetes. A non-pharmacological effort to maintain cognitive function is brain gym exercises. This study aimed to determine the effect of brain gym exercises on improving cognitive function among elderly people with diabetes mellitus at Singkawang Utara 1 Public Health Center. This research used a pre-experimental design with a pretest and posttest without control group. A total of 30 elderly with diabetes mellitus were selected using simple random sampling. The intervention consisted of brain gym sessions conducted for 30 minutes, three times a week for two weeks. Cognitive function was measured using the Mini Mental Status Examination (MMSE) and analyzed with the Wilcoxon test. The results showed a significant effect with p = 0.032 (p < 0.05), indicating that brain gym exercises significantly improved cognitive function in the elderly. In conclusion, brain gym is effective in enhancing cognitive function among elderly patients with diabetes mellitus.